Smart windows for modulation of infrared heat - Khoo, Steffi Shu Fern (Nanyang Technological University, 2020)
Smart windows technologies have been an area of great research interest to minimize energy consumption from commercial and residential buildings. Smart windows are known to have high energy efficiency and adaptability in climate change and are often classified as electrochromic, photochromic or thermochromic windows. Prior research on electrochromic windows have found that Tungsten Trioxide (WO3) is the best electrochromic material and that Electrochromic Photonic Crystals (EPC) technology involved periodic inverse opal (IO) structures that can enhance the modulation of infrared radiation. Previous studies on TiO2-WO3 and SnO2-WO3 hybrid systems have achieved several improvements for electrochromic performance. However, those compositions remain limitations of transparency, electrochromic stability. A novel MoxSnO2/ α-WO3 EPC framework is thus fabricated to block at least 80% NIR radiation in the coloured state, enables up to 90% of visible light transmittance in bleached state and retain the electrochromic stability for at least 900 cycles. In this project, the novel MoxSnO2 EPC is fabricated and tested to optimize the concentration of Molybdenum (Mo). The results have shown that 20 mol.% Molybdenum is the optimal concentration.